Kentuckians in Gray : Confederate Generals and Field Officers of the Bluegrass State - Hewitt, Lawrence L.; Allardice, Bruce S. (Book collections on Project MUSE., 2008)
Kentuckians in Gray is a comprehensive collection of biographical sketches of key Confederate military personnel from the Bluegrass state. In addition to providing short profiles of lesser-known colonels, lieutenant colonels, and majors, the book vividly details significant players including Tyree H. Bell, Abraham Buford, Thomas James Churchill, and Richard Taylor. This work will be a standard reference for historians and Civil War buffs of the Bluegrass for years to come.